A Fault and Islanding Detection Scheme using Differential Positive Sequence Power Angle for a Microgrid - Ansari, Salauddin; Gupta, Om Hari (Distributed Generation & Alternative Energy Journal, 2022)
Implementation of distributed generation (DG) fault and islanding detection in a microgrid are two difficult jobs to complete. Efforts by many researchers to develop solutions to these a kind of challenges are ongoing. Still, there is hardly any scheme that can detect and distinguish both the fault and islanding events. To detect and differentiate between fault and islanding events, this article presents a Differential Positive Sequence Power Angle (DPSPA)-based protection technique. The scheme is widely examined considering different working conditions of a microgrid such as DG disconnection, DG penetration, different fault parameters like fault type, fault resistance, fault location, fault inception angle, fault during single-pole tripping (STP), simultaneous faults, and evolving faults. Tests were also performed for non-fault cases like load switching, capacitor switching, sectional cut-off, DG disconnection, and impact of noise and sampling frequency. Furthermore, the scheme’s outcomes have been compared to that of recent protection schemes. Finally, using the OP4510 real-time simulator, the proposed approach is validated in an online environment. The results show that the proposed DPSPA-based scheme can be a notable scheme to protect a microgrid in a wide variety of situations.